Position of ICMW in ASEAN and A Glimpse Into The Philippine Practise on Migration - Saidatul Nadia Abd Aziz; Salawati Mat Basir (Jurnal Hukum Volkgeist, 2022)
In ASEAN, Philippines was among the first to ratify the International Convention on the Protection of the Rights of All Migrant Workers(ICMW) and have the best practice thus far. This article demonstrates that, despite the barriers and incompatibilities with national laws, the Convention, which is primarily a human rights instrument aimed at protecting the fundamental rights of all migrants, could assist ASEAN in ensuring a holistic and sustainable migration management that considers the needs of a whole approach and support from all parties involved, including but not limited to the government. Part I of the article will go through the history of the convention's adoption, followed by Part II on the position of ASEAN's migration policies and practice, Part III will discuss on the Philippines practices on ICMW and Migration management, and Part IV will provide recommendations.